Lifestyle Habits Related to Internet Use in Adolescents: Relationships between Wellness, Happiness, and Mental Health - Sigita Lesinskienė; Rokas Šambaras; Agnė Butvilaitė; Justina Andruškevič; Margarita Kubilevičiūtė; Urtė Stanelytė; Severija Skabeikaitė; Izabelė Jūraitytė; Ieva Ridzvanavičiūtė; Kamilė Pociūtė; Natalja Istomina (MDPI AG, 2024)
Background: Studies in recent years have shown a significant increase in problematic internet use. Prolonged internet usage negatively impacts various aspects of adolescents' lifestyles. Methods: The survey was conducted in three Lithuanian cities-Vilnius, Klaipėda, and Molėtai-between October and December of 2023. The survey involved students between the ages of 12 and 16. The participants completed a questionnaire that included questions about wellness and happiness, the Internet Addiction Test (IAT), and the Strengths and Difficulties Questionnaire (SDQ). Our study aimed to investigate problematic internet use among Lithuanian adolescents and its relationships with wellness, happiness, and mental health. Results: This study included 1412 adolescents, with a mean age of 14.41 ± 1.20, with the sample composed of 52.3% boys. Boys indicated that they felt healthier and happier than girls (69.4% vs. 47.4%; 51.4% vs. 29.6%), p < 0.001. A total of 20.8% of students had IAT scores that reflect a normal level of internet usage. For IAT, the average score of girls was statistically significantly higher than that of boys (41.87 ± 12.24 vs. 39.96 ± 12.37), p < 0.001. The IAT score was higher in the group of students who felt less happy and healthy, had more frequent headaches or abdominal pain, and had problems with sleep, p < 0.001. A statistically significant, positive weak correlation was found between students' IAT scores and SDQ internalizing and SDQ externalizing scores (r = 0.366; r = 0.385, p < 0.001). Conclusions: Prolonged internet use is arising as a serious problem among adolescents. Negative feelings, unhappiness, and poor emotion regulation have an association with internet addiction. Also, the female gender may be more associated with possible internet addiction. The results of this study can serve as initial steps toward developing preventive interventions.